Photoelectrocatalytic Performance of Benzoic Acid on TiO2 Nanotube Array Electrodes - Hongchong Chen; Jinhua Li; Quanpeng Chen; Di Li; Baoxue Zhou (International Journal of Photoenergy)
The photoelectrocatalytic performance of benzoic acid on TiO2 nanotube array electrodes was investigated. A thin-cell was used to discuss the effect of the bias voltage, illumination intensity, and electrolyte concentration on the photoelectrocatalytic degradation efficiency of benzoic acid. The photogenerated current-time (I-t) profiles were found to be related to the adsorption and the degradation process. The relationship between the initial concentration and the photocurrent peaks (I0ph) fits the Langmuir-type adsorption model, thus confirming that the adsorption of benzoic acid on TiO2 nanotube arrays (TNAs) was single monolayer adsorption. At low concentrations, the I-t profiles simply decay after the initial transient peak due to the sufficient holes on the TNAs which would oxidize the benzoic acid quickly. However, the I-t profiles varied with increasing benzoic acid concentrations because the rate of diffusion in the bulk solution and the degradation of the intermediate products affect the photoelectrocatalysis on the electrode surface.